Character Education Learning Using The Contextual Teaching Learning (CTL) Approach for Civics Learning - Rukua, La Kasman; Siregar, Eveline; Wirasti, R A Murti Kusuma (LPPM Undiksha, 2021)
The development of Industry 4.0, the rapid advancement of science and technology demands many changes from various human lives. In this era, there were also many positive and negative impacts, but they did not protect themselves, especially teenagers, with potential high school characters, their behavior distorted moral and moral decadence among teenagers. To be able to adapt to these changes make education as a spearhead and a powerful antidote especially character education. This research is development (R&D). In this research purpose to develop a character education learning module contextual teaching and learning (CTL) approach of PKn subject. This research method refers to the development model of Derek Rowntree and Dick &Carry. The development procedure through three stages, the first stage uses Dick & Carry model until the seventh step is selecting and developing. In the second and third stages using Derek Rowntree model. Review process through reviews of media expert and instructional design expert and reviews of media and language experts. To the target, a one-to-one test was conducted, small group test and field test. Evaluation is carried out until summative evaluation with calculations N-Gain Score to measure the level of effectiveness. The result of effectiveness state that the student character learning module in PKn subject is effective in used.